Troubling Unintended Harm of Heroic Discourses in Social Justice Leadership - Kim, Taeyeon; Mauldin, Courtney (Frontiers in Education, 2022)
We aim to problematize the ways in which school leaders who seek social justice conflate heroic leadership discourses in their practices. Using qualitative data collected from an urban school principal, this study examines heroic metaphors utilized by the principal when describing social justice leadership and how heroic-centered approaches contradict with achieving social justice goals in school. The findings suggest that the principal’s idea of social justice leadership relies on discourse around “battles to win”, a savior complex, and seeing herself as the central model for driving change. Such heroic discourses reflect the principal’s sole reliance on herself as a savior for her staff and community, which ultimately contradicted the social justice ideals that she sought to accomplish. Our inquiry provides a window to problematize heroic discourse embedded in social justice leadership and address how school leaders must be cognizant to how their practices might conflate with social justice outcomes.